Effects of the efficacy of the Yi Shen Tiao Gan formula on aromatase inhibitor associated musculoskeletal syndrome: a randomized controlled trial - Zhang, Yan; Chu, Meiling; Ye, Meina; Cheng, Yiqin; Cong, Hui; Yin, Yulian; Chen, Hongfeng (Frontiers in Pharmacology, 2025)
BackgroundAromatase inhibitor-induced musculoskeletal syndrome (AIMSS) has emerged as a major cause of treatment discontinuation in hormone receptor-positive patients treated with aromatase inhibitors. There are currently no standardized guidelines or universally accepted treatments for AIMSS. Therefore, this exploratory study aimed to preliminarily evaluate the efficacy and safety of Yi Shen Tiao Gan formula in AIMSS patients.MethodsA total of 136 patients with AIMSS were included in this single-center, randomized, controlled, single-blind trial and were randomised into the treatment and control groups at a ratio of 1:1. All patients were routinely given Caltrate D. Patients in the treatment group took Breast surgery formula combined with Yi Shen Tiao Gan formula and control group took Breast surgery formula twice a day. The treatment period of Chinese medicine was 3 months as one course of treatment. The clinical efficacy of two courses of treatment was observed in this study. The study observed and compared the following indicators between the two groups: the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, Traditional Chinese Medicine symptom and sign scores, bone mineral density, bone metabolism biochemical indicators, bone metabolism-related hormones and safety assessments.ResultsIn total, 108 participants were included in the analysis. Before and after treatment, the total WOMAC score of both groups of patients significantly decreased (p < 0.05), with the pain subscale score of the treatment group being significantly lower than that of the control group (p < 0.05). The TCM symptom and sign score significantly decreased in both groups (p < 0.05), with a more pronounced reduction in the treatment group (p < 0.05). The bone mineral density T-score of both groups of patients showed a downward trend. The decrease in the left femoral bone density T-score was smaller in the treatment group, while the decline in the lumbar spine bone density T-score was slower in the control group. There was no significant difference in bone metabolism levels between the two groups (p > 0.05), but the decrease in β-CTX was slightly slower in the treatment group of the AI + OFS population compared to the control group. After applying Bonferroni correction for multiple testing, these associations did not reach statistical significance. No serious adverse events were observed in either group.ConclusionThe YSTG formula significantly reduced WOMAC scores, improving pain, stiffness, physical function in patients with AIMSS, and alleviating the traditional Chinese medicine symptoms and signs of liver and kidney deficiency, thereby enhancing the overall quality of life for patients.Clinical Trial Registrationhttp://www.chictr.org.cn, identifer ChiCTR2200057785.